Competency-Based Evaluation in Higher Education—Design and Use of Competence Rubrics by University Educators - Velasco-Martínez, Leticia Concepción; Tójar-Hurtado, Juan Carlos (Canadian Center of Science and Education, 2018)
Competency-based learning requires making changes in the higher education model in response to current socio-educational demands. Rubrics are an innovative educational tool for competence evaluation, for both students and educators. Ever since arriving at the university systems, the application of rubrics in evaluation programs has grown progressively. However, there is yet to be a solid body of knowledge regarding the use of rubrics as an evaluation tool. This study analyzes the use of rubrics by 150 teachers at 5 Spanish universities. The comparative analysis allows us to determine how these rubrics are being used to assess (or not) competencies. This study examines the educators' intentions and the pedagogical aspects that are considered in the design and application of rubrics. The results and conclusions may lead to suggestions for improvements and strategies that may be implemented by university professors when creating appropriate competency-based scoring rubrics.
Keywords: Competencia en educación; Evaluation method; Competences; Competency-based education; Higher education; Scoring rubric